Status of agroforestry systems established from 2011 to 2018 under the Program for Payment of Environmental Services in three regions of Costa Rica - Quesada Quesada, Juan José (2023)
The National Forest Financing Fund (FONAFIFO) contemplates a payment method for environmental services (PES) that seeks to recover forest cover. Within this modality are agroforestry systems (AFS) which objective is to combine trees with agricultural production systems. However, the composition and status of these systems is currently unknown. In order to characterize the SAFs subjected to the PSA in Costa Rica, an analysis of the projects formalized by FONAFIFO between 2011 and 2018 was carried out in the regional offices San Carlos, San José Oriental and San José Occidental.  Technical studies of 527 projects and the respective certified reports were reviewed. Project identification, type of regency, planted area, tree species and number of trees per species, associated agricultural component, agroforestry technology, and reported management were recorded. The information was tabulated and analyzed using descriptive statistics. A predominance of agroforestry systems in coffee (43%) associated mainly with the tree species Erythrina sp. as a multi-use tree concentrated in the Los Santos and Pérez Zeledón area. Block systems were found in second place (32%), predominating teak (Tectona grandis), cedar (Cedrela odorata) and melina (Gmelina arborea) located in the North Zone and Central Pacific. A few reports of silvicultural practices and phytosanitary status were found. Weed control was the most reported practice. It is necessary to improve the monitoring and recording of information on the projects in order to have evidence of silvicultural management.